2022
DOI: 10.1371/journal.pone.0269020
|View full text |Cite
|
Sign up to set email alerts
|

Client and healthcare worker experiences with differentiated HIV treatment models in Eswatini

Abstract: Introduction Universal access to antiretroviral therapy (ART) is a cornerstone of Eswatini’s national HIV strategy, and the number of people on ART in the country more than tripled between 2010 and 2019. Building on these achievements, the Ministry of Health (MOH) is scaling up differentiated service delivery, including less-intensive differentiated ART (DART) models for people doing well on treatment. We conducted a mixed-methods study to explore client and health care worker (HCW) perceptions of DART in Eswa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although most responses were positive in terms of working conditions, a minority of respondents in all three countries stated that the introduction of DSD models reduced their job satisfaction, due mainly to additional administrative duties and lack of human and nancial resources at their facilities. This was more commonly reported by South African respondents and mirrors ndings from studies in Zimbabwe (34) and Eswatini (31), in which providers reported that having to ll prescriptions for community-based models added to their job burdens.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although most responses were positive in terms of working conditions, a minority of respondents in all three countries stated that the introduction of DSD models reduced their job satisfaction, due mainly to additional administrative duties and lack of human and nancial resources at their facilities. This was more commonly reported by South African respondents and mirrors ndings from studies in Zimbabwe (34) and Eswatini (31), in which providers reported that having to ll prescriptions for community-based models added to their job burdens.…”
Section: Discussionmentioning
confidence: 53%
“…Our results also add to the existing body of research on self-reported provider workload following DSD implementation in other sub-Saharan African countries. Healthcare workers from Eswatini reported decreased workload, reduced clinic congestion, and shorter patient waiting times following the implementation of DSD models (31). Providers in Mozambique reported an overall improvement in quality of care due to reduced provider workload, which allowed them to attend to more complicated patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of previous studies assessing overall satisfaction with routine HIV care in high HIV burden settings [ 24 , 25 , 26 ]. A study in Eswatini found that 96% of study participants were satisfied with their current ART delivery model, and 90% recommended it to others [ 17 ]. Recipients of care from Khayelitsha in Cape Town, South Africa, also reported generally positive experiences with DSD model care [ 27 ], and 64.2% of those enrolled in DSD model care in Uganda reported high satisfaction with the treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recipients of care from Khayelitsha in Cape Town, South Africa, also reported generally positive experiences with DSD model care [ 27 ], and 64.2% of those enrolled in DSD model care in Uganda reported high satisfaction with the treatment [ 18 ]. These prior studies did not compare satisfaction with DSD model care with conventional care [ 17 , 18 , 28 ]. This study contributes to the knowledge base by providing this comparison, finding that those in DSD models are more likely to express satisfaction with their care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation